ANALISIS SISTEM INFORMASI GEOGRAFIS DALAM PERWILAYAHAN KOMODITAS KAKAO (Theobroma cacao L.) DI KABUPATEN ENREKANG - Ilham Ilham; Andi Nuddin; Andi Adam Malik (Jurnal Pendidikan Teknologi Pertanian, 2017)
Climatic data and information is indispensable as an initial selection in the identification of potential land and the determination of agricultural commodity development strategies in an area. Opportunities to manipulate climate data are very small and unpredictable. Each plant has an ideal environment for living, as well as the cocoa plant. Cocoa plant growth and development is strongly influenced by the environment. Climatic factors that greatly affect the cacao plant, among others elevation, rainfall, dry month and the air temperature. Therefore, it is necessary to cross the cocoa commodity by looking at the agro-climatic suitability class with the overlay method based on Geographic Information System (GIS) of Enrekang Regency. The results showed that the grade of agroclimate suitability of cocoa commodity was dominated by class N or not appropriate. The dominant area is 45.7% (83.262.97 Ha) and the smallest class is S3 or marginal, with 7.5% (13,666.75 Ha) of total research area. The areas suitable for planting cocoa are in the suitability class S1 or very appropriate, with an area of 33,390.46 Ha or about 18.3% of the total area of Enrekang Regency.